COVID-19 Vaccine: Examining Nurses Attitude and Willingness to accept the inoculation in North Western Nigeria - Abdullahi Haruna Ibrahim; Muhammad Awwal Ladan; Umar Yunusa; Murtala Hassan Hassan; Hamza Abubakar; Sulaiman Tukuntawa Abdul'Aziz (IJNP (Indonesian Journal of Nursing Practices), 2022)
Background: Healthcare providers are the first line of information in pandemics and the last line of support during infections spread.Objective: The study was conducted to examine Nurses Attitude and Willingness to accept COVID-19 vaccine in Northern Nigeria.Methods: Cross-sectional design and systematic sampling technique were used for the study where 300 pretested structured questionnaires were distributed to nurses attending Nursing and Midwifery Council of Nigeria’s Mandatory Continuing Professional Development Programme in Kano, Jigawa, Kaduna and Katsina states of Northwestern Nigeria. 89.3% of the questionnaires were successfully retrieved and analysed using frequency tables and spearman’s correlation coefficient.Result: The result revealed that majority (67.3%) had a positive attitude towards vaccines in general but 89.6% of the respondents were not willing to receive the COVID-19 vaccine. Spearman’s correlation analysis revealed a significant positive correlation between Knowledge of COVID-19 (ρ =0.402, p0.01), having long term medical condition (ρ =0.492, p0.01), highest educational qualification (ρ =0.291, p0.01), female gender (ρ =0.160, p0.01) and willingness to receive COVID-19 vaccine among the respondents. Significant positive correlation was also observed between age (ρ =0.186, p0.01) and refusing a recommended vaccine in the past. Significant negative correlations were observed between refusing a recommended vaccine in the past (ρ =-0.661, p0.05) and willingness to receive COVID-19 vaccine, knowledge of COVID-19 (ρ = - 0.132, p0.01), refusing a recommended vaccine in the past (ρ = - 0.132, p0.01) and years of working experience.Conclusion: It was recommended that awareness campaigns needs to be instituted targeting the eradication of COVID-19 vaccine hesitancy among all healthcare providers.